Clarithromycin ameliorates pulmonary inflammation induced by short term cigarette smoke exposure in mice. (December 2015) - Nakamura, Masuo; Wada, Hiroo; Honda, Kojiro; Nakamoto, Keitaro; Inui, Toshiya; Sada, Mitsuru; Watanabe, Masato; Takata, Saori; Yokoyama, Takuma; Saraya, Takeshi; Kurai, Daisuke; Ishii, Haruyuki; et al.
Abstract: Background: Cigarette smoking is considered to be one of major causes of acute worsening of asthma as well as chronic obstructive pulmonary disease (COPD). Macrolide antibiotics have been reported to reduce the risk of exacerbations of COPD, and possibly neutrophilic asthma. However, the effect of clarithromycin (CAM) on pulmonary inflammation caused by short term exposure to cigarette smoke still remains to be investigated. Methods: C57BL/6J female mice were daily exposed to tobacco smoke using a tobacco smoke exposure system, or clean air for 8 days, while simultaneously treated with either oral CAM or vehicles. Twenty four hours after the last exposure, mice were anaesthetized and sacrificed, and bronchoalveolar lavage (BAL) fluids were collected. Cellular responses in BAL fluids were evaluated. Levels of cytokine mRNA in the lung tissues were measured by quantitative RT-PCR. Paraffin-embedded lung tissues were evaluated to quantitate degree of neutrophil infiltration. Results: The numbers of total cells, macrophages and neutrophils in the BAL fluid of smoke-exposed mice were significantly increased as compared to clean air group. These changes were significantly ameliorated in CAM-treated mice. The lung morphological analysis confirmed decrease of neutrophils by CAM treatment. Studies by quantitative PCR demonstrated CAM treatment significantly reduced lung expression levels of IL-17A, keratinocyte-derived chemokine (KC), granulocyte-macrophage colony stimulating factor (GM-CSF) and MMP-9 induced by cigarette smoke. Conclusion: We demonstrate that CAM administration resolves enhanced pulmonary inflammation induced by short term cigarette smoke exposure in mice.